2014
DOI: 10.1590/0102-311x00174513
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with undernourishment among people 20 years old or over with HIV/AIDS, attending public health services in the São Paulo municipality, Brazil

Abstract: The study evaluated the nutritional status of 629 people living with HIV/AIDS attended at 12 specialized services of São Paulo's Municipal Health Department, Brazil. Data were obtained from medical records and through interviews during nutritional consultation. We used the classification criteria established by World Health Organization to assess malnourished individuals, a BMI < 18.5kg/m2. The prevalence of malnutrition in people with AIDS is 3.12 times that observed among people with HIV, and among people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…It was also similar to studies conducted at Tanzania, Nepal, and Senegal, which showed rates of malnutrition of 18.4% 19.9%, and 22.9%, respectively 25,30,31. However, the finding of this report was higher compared to findings from studies from Brazil (7.3%), Zimbabwe (10%), Iran (11.1%), and Dilla Ethiopia (12.3%) 24,26,27,32. This difference might be related to socio-economic differences and seasonal variation within the studies.…”
Section: Discussionsupporting
confidence: 86%
“…It was also similar to studies conducted at Tanzania, Nepal, and Senegal, which showed rates of malnutrition of 18.4% 19.9%, and 22.9%, respectively 25,30,31. However, the finding of this report was higher compared to findings from studies from Brazil (7.3%), Zimbabwe (10%), Iran (11.1%), and Dilla Ethiopia (12.3%) 24,26,27,32. This difference might be related to socio-economic differences and seasonal variation within the studies.…”
Section: Discussionsupporting
confidence: 86%
“…It is important to note that tobacco nicotine alters the viscosity of the blood and alcohol leads to loss of critical judgment, behavior, concentration and awareness. On the other hand, illicit drugs, such as cocaine and marijuana, cause a symptomatic exacerbation, such as tachycardia, convulsion, ventricular arrhythmias, shakes and hallucinations, affecting the sleep quality of such clients (23) .…”
Section: Discussionmentioning
confidence: 99%
“…The cause of poor sleep quality may be related to the use of antiretroviral agents as well as alcohol and drug withdrawal. It is worth mentioning that patients who use medications on a daily basis tend to have their circadian cycle modified (2,(18)(19)(20)(21)(22)(23) . In addition, fatigue, which is characterized by the accumulation of lactic acid in the myocytes, can corroborate this picture.…”
Section: Discussionmentioning
confidence: 99%